Structural changes in the Russian health care system: Do they match European trends? - Sergey Shishkin; Igor Sheiman; Vasily Vlassov; Elena G. Potapčik; Svetlana Sazhina (Health Economics Review, 2022)
Background: In the last two decades, health care systems (HCS) in the European countries have faced global challenges and have undergone structural changes with the focus on early disease prevention, strengthening primary care, changing the role of hospitals, etc. Russia has inherited the Semashko model from the USSR with dominance of inpatient care, and has been looking for the ways to improve the structure of service delivery. This paper compares the complex of structural changes in the Russian and the European HCS. Methods: We address major developments in four main areas of medical care delivery: preventive activities, primary care, inpatient care, long-term care. Our focus is on the changes in the organizational structure and activities of health care providers, and in their interaction to improve service delivery. To describe the ongoing changes, we use both qualitative characteristics and quantitative indicators. We extracted the relevant data from the national and international databases and reports and calculated secondary estimates. We also used data from our survey of physicians and interviews with top managers in medical care system. Results: The main trends of structural changes in Russia HCS are similar to the changes in most EU countries. The prevention and the early detection of diseases have developed intensively. The reduction in hospital bed capacity and inpatient care utilization has been accompanied by a decrease in the average length of hospital stay. Russia has followed the European trend of service delivery concentration in hospital-physician complexes, while the increase in the average size of hospitals is even more substantial. However, distinctions in health care delivery organization in Russia are still significant. Changes in primary care are much less pronounced, the system remains hospital centered. Russia lags behind the European leaders in terms of horizontal ties between providers. The reasons for inadequate structural changes are rooted in the governance of service delivery. Conclusion: The structural transformations must be intensified with the focus on strengthening primary care, further integration of care, and development of new organizational structures that mitigate the dependence on inpatient care.
Keywords: 330; Health care system; Health service provision; Inpatient care; Primary care; Semashko model; Structural changes